Nurse training from the perspective of integral care and teamwork (Research, Society and Development, 2021)
Providing comprehensive care is important for the patient to have his needs met at different angles. This study aimed to analyze the students' perception of the integrality of care and teamwork in the process of their professional training. This is an exploratory, descriptive study, with a quantitative cross-sectional approach. 191 nursing students from a private university in Aracaju participated in the research from the sixth to the tenth period. With a predominance of female responses, the responses showed the importance of starting activities that encourage teamwork and comprehensive care even during professional training. It is extremely important to include team work and comprehensive care in the curriculum, being considered the first step towards achieving quality assistance in all health systems.